2012
DOI: 10.1016/j.athoracsur.2012.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Changing Expectations for Neurological Outcomes After the Neonatal Arterial Switch Operation

Abstract: Background Expectations for outcomes after the neonatal arterial switch operation (ASO) continue to change. This cohort study describes neurodevelopmental outcomes at age 12 months after neonatal ASO, and analyzes both modifiable, and non-modifiable factors for association with adverse outcomes. Methods ASO patients (n=30) were enrolled in a prospective outcome study, with comprehensive clinical data collection over the first 12 months of life. Brain magnetic resonance imaging (MRI) was done preoperatively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
96
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 27 publications
2
96
1
Order By: Relevance
“…A number of studies have reported the rate of preoperative brain injury on MRI in young infants undergoing surgery for CHD to be between 25% and 40%. [12][13][14][15][16] In noncardiac infant populations, MRI has been shown to be superior to HUS in sensitivity and specificity for detection of brain injury, which included white matter abnormalities or periventricular leukomalacia (PVL), 6 ischemia, 17 and hemorrhage, 6,17 but this comparison has not been made in infants with CHD.The purpose of the current study was to assess the utility of preoperative HUS in a cohort of newborns and infants who also underwent preoperative MRI as part of prospective research studies of brain injury in the setting of surgery for CHD. …”
mentioning
confidence: 99%
“…A number of studies have reported the rate of preoperative brain injury on MRI in young infants undergoing surgery for CHD to be between 25% and 40%. [12][13][14][15][16] In noncardiac infant populations, MRI has been shown to be superior to HUS in sensitivity and specificity for detection of brain injury, which included white matter abnormalities or periventricular leukomalacia (PVL), 6 ischemia, 17 and hemorrhage, 6,17 but this comparison has not been made in infants with CHD.The purpose of the current study was to assess the utility of preoperative HUS in a cohort of newborns and infants who also underwent preoperative MRI as part of prospective research studies of brain injury in the setting of surgery for CHD. …”
mentioning
confidence: 99%
“…Numerous studies have reported that PDA leads to lower cerebral oxygenation, 10-12 and Lemmers et al 13 previously reported that infants with PDA had mean arterial blood pressure and regional cerebral oxygen saturation that were significantly lower than those of control infants (mean arterial blood pressure, 33 ± 5 mm Hg vs 38 ± 6 mm Hg; regional cerebral oxygen saturation, 62% ± 9% vs 72% ± 10%, for PDA and controls, respectively). Although lower cerebral oxygenation has been shown to be associated with worse neurodevelopmental outcome in term infants undergoing surgery for congenital heart disease, [14][15][16] this relationship is not addressed in the current article. In preterm infants, lower cerebral volume, specifically decreased total brain volume and deep nuclear gray matter volume, is known to be associated with worse cognitive and motor development and a higher incidence of cerebral palsy.…”
Section: Department Of Pediatrics Section Of Critical Care Baylor Cmentioning
confidence: 82%
“…A number of studies have reported the rate of preoperative brain injury on MRI in young infants undergoing surgery for CHD to be between 25% and 40%. [12][13][14][15][16] In noncardiac infant populations, MRI has been shown to be superior to HUS in sensitivity and specificity for detection of brain injury, which included white matter abnormalities or periventricular leukomalacia (PVL), 6 ischemia, 17 and hemorrhage, 6,17 but this comparison has not been made in infants with CHD.…”
Section: What This Study Addsmentioning
confidence: 99%